Construction of compact complex surfaces uniformized by the unit ball - Rossetti, Alessandro (Stellenbosch : Stellenbosch University, 2013)
Degree completed in collaboration with the University of Bordeaux 1, under the ALGANT Consortium (http://www.algant.eu/about.php). The thesis is also available at: http://www.algant.eu/documents/theses/rossetti.pdf.